EPIDEMIOLOGICAL PROFILE OF CUTANEOUS SUPERFICIAL MYCOSES IN SOUTH, BRAZIL - L. F. Rocha; F. M. Bittencourt; K. M. Hernandes; S. M. B. Gonçalves; C. M. G. Rodrigues; V. Z. Bergamo; L. N. Calil; A. Mezzari (Scientific Electronic Archives, 2018)
Cutaneous superficial mycoses appear as lesions on the skin, hair and nails. The highest prevalence is of fungal infections caused by the fungi of the genus Microsporum, Epidermophyton, Trichophyton, Candida and Malassezia. These mycoses are common in tropical regions and are commonly neglected due to lack of patient knowledge, difficult diagnosis and lack of access to health facilities, which makes them a public health problem. In research, mycological examination of patients using Basic Health Units (BHU) was carried out in order to diagnose mycoses. Through this action, it was possible to diagnose and refer to the appropriate treatment 5359 patients, seeking to improve their quality of life. From the results of the mycological exams of these patients during the period from 2011 to 2016, it was possible to trace the epidemiological profile of the State of Rio Grande do Sul and the most prevalent species, contributing to the accomplishment of measures in public health.